Evaluative conditioning leads to differences in the social evaluation of prototypical faces. (January 2017) - Kocsor, Ferenc; Bereczkei, Tamás
Abstract: The majority of social psychological studies using evaluative conditioning have focused on how change is triggered in emotional dispositions to human faces. Our aim was to test whether non-social affective information are transferred from individual faces to composites. We created composites of individual faces which were preceded by pictures with either positive or negative content. We found that the composite made from faces conditioned with high valence images was judged as the more trustworthy. This suggests that in the evaluative conditioning task the valence values of the images that have no social meaning are associated to faces, then transferred to other facial stimuli which share traits with the previously presented faces. Evaluative conditioning, in this way, leads to the emergence of social judgments. Therefore we propose that associative learning and generalization mediate the formation of face-prototypes, a mechanism which may play a central role in the evaluation of unknown faces. Highlights: Facial images were preceded by images with either high or low valance. We tested whether non-social information will be transferred to composite faces. Composites made from positively conditioned faces were chosen as the more trustworthy. Exposure to faces and acquisition of socially irrelevant information shape prototypes. The evaluation of unknown individuals is based on associative processes.